Bryobionta of Emerald Network of Ukraine under protection of the Bern Convention (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The article describes the bryophyte species that are listed in Appendix I of the Bern Convention, adopted in 1979, that are found in Ukraine. These are Dicranum viride (Sull. & Lesq.) Lindb. (Dicranaceae), Dichelyma capillaceum (With.) Myrin (Fontinalaceae), Buxbaumia viridis (Mougeot ex Lam. & DC) Mougeot & Nestler (Buxbaumiaceae), Meesia longiseta Hedw. (Meesiaceae), Hamatocaulis (Drepanocladus) vernicosus (Mitt.) Hedenäs (Amblystegiaceae), and Mannia triandra (Scop.) Grolle (Aytoniaceae). The Ukrainian and Latin names of species, their codes from the Standard Data form of the Emerald website, the biogeographical region of occurrence, general characteristics of the species, its taxonomic positions, scientific value, distribution in the world and in Ukraine, with the indication of physiographic zones and landscapes of Ukraine, including Ukrainian Carpathians (Zacarpattia, Carpathians, Prykarpattia), Crimea (Mountain Crimea, Southern Coast Crimea), Ukrainian Polissia, Nemoral zone (including Opillia, Roztochchia, Western Forest-steppe), Forest-Steppe zone, Steppe zone (including Steppe Crimea), habitat, habitat conditions, photographic image of a species, key factors of the abatement, adopted protection activities, codes of the Emerald sites where the species occurs, necessary protection activities, and the list of literary sources are indicated for each species. Therefore, due to the urgency of the study of plant species, including non-native species included in the annexes of the Berne Conference and the design of the Emerald Nature Network of Ukraine, it is necessary to strengthen the study of populations of these rare species and biotopes in which they grow. This is especially important for species of bryophytes, as the findings of most of them were made long ago. These materials will be used when designing the Emerald Network of Ukraine.
Keywords: Berne Convention, Bryobionta of Ukraine, Emerald network of Ukraine.